THE EFFECT OF PROFITABILITY, LEVERAGE, INSTITUTIONAL OWNERSHIP AND FIRM SIZE ON TAX AVOIDANCE: EMPIRICAL STUDY ON MANUFACTURING COMPANIES LISTED ON IDX FOR THE 2017-2019 PERIOD - Novia Rahmawati; Djoko Wahyudi (Universitas Muhammadiyah Tapanuli Selatan, 2021)
The receipt of public contributions, which will subsequently enter the state treasury, is the main supply of governmental earnings. For the state, taxes are a source of income, while for companies, taxes are a burden that reduces the company's net profit. Reducing net income makes many companies use several ways to minimize their taxes, one of which is by doing tax evasion. The method is legal, meaning it does not contradict any tax laws. The goal of this study is to explore and assess the impact of tax evasion on financial capability, leverage, institutional ownership, and firm size. The purposive sampling method was used to select a sample of 237 industrial businesses listed on the Indonesia Stock Exchange (ISE) between 2017 and 2019. Multiple linear regressions were applied to analyze the data. The findings of this study display that institutional ownership has a considerable influence on tax evasion, whereas profitability, leverage, and firm size have no substantial influence on tax evasion.